3(5x-5+6)+2(3x-5+10)=

Simple and best practice solution for 3(5x-5+6)+2(3x-5+10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5x-5+6)+2(3x-5+10)= equation:


Simplifying
3(5x + -5 + 6) + 2(3x + -5 + 10) = 0

Reorder the terms:
3(-5 + 6 + 5x) + 2(3x + -5 + 10) = 0

Combine like terms: -5 + 6 = 1
3(1 + 5x) + 2(3x + -5 + 10) = 0
(1 * 3 + 5x * 3) + 2(3x + -5 + 10) = 0
(3 + 15x) + 2(3x + -5 + 10) = 0

Reorder the terms:
3 + 15x + 2(-5 + 10 + 3x) = 0

Combine like terms: -5 + 10 = 5
3 + 15x + 2(5 + 3x) = 0
3 + 15x + (5 * 2 + 3x * 2) = 0
3 + 15x + (10 + 6x) = 0

Reorder the terms:
3 + 10 + 15x + 6x = 0

Combine like terms: 3 + 10 = 13
13 + 15x + 6x = 0

Combine like terms: 15x + 6x = 21x
13 + 21x = 0

Solving
13 + 21x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 21x = 0 + -13

Combine like terms: 13 + -13 = 0
0 + 21x = 0 + -13
21x = 0 + -13

Combine like terms: 0 + -13 = -13
21x = -13

Divide each side by '21'.
x = -0.619047619

Simplifying
x = -0.619047619

See similar equations:

| 4(6a-7)=-52 | | 7/-3=21/x | | 7/-3=24/x | | 4(3c-5)=-32 | | 4(3c-5)=32 | | 7/-3=7/x | | 5(-5c+2)=35 | | 3=1/5k | | x*0.6=0.84 | | x+1.8=3.25 | | 4(-4a-3)=36 | | x-1.24=1.9 | | x+2.4=4.1 | | 4(x-7)=39 | | 6z-29=3z-8 | | 3(3x-3)y=32 | | 6c-17=3c-35 | | 9z-24=5z-8 | | 60=13m+a | | 4x+6=-x+36 | | logE=17.8 | | 6y-5x-5=6(xy)-5 | | (-3a-b)+(2a-5b)= | | 8888=500 | | 2-3y=px | | 18-Y=(-18) | | 10z-93=4z-45 | | 4g-11=13-2g | | 5a+6=3a+10 | | y-13=36 | | 3(4f-7)=-45 | | 10x^(1/3)-10x |

Equations solver categories